Use of Gibberellic Acid Treatments to Improve Health and Yield of HLB-Affected Sweet Orange Trees: Concerns and Considerations (Part 2 of 2) - Tripti Vashisth (EDIS)
This publication discusses fruit quality and gibberellic acid use in citrus. Written by T. Vashisth, and published by the UF/IFAS Horticultural Sciences Department, February 2023.